2021
DOI: 10.1111/mcn.13158
|View full text |Cite
|
Sign up to set email alerts
|

Engaging family members in maternal, infant and young child nutrition activities in low‐ and middle‐income countries: A systematic scoping review

Abstract: The influence of fathers, grandmothers and other family members on maternal, infant and young child nutrition practices has been well documented for decades, yet many social and behavioural interventions continue to reach only mothers. While recent guidelines recommend involving fathers, grandmothers and other family members in maternal and child nutrition, we lack a comprehensive review of interventions that have engaged them. This scoping review aimed to address this gap by describing social and behavioural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 141 publications
0
18
0
1
Order By: Relevance
“…Inclusion of fathers has positively influenced retention and engagement of mothers [ 62 ] and maternal and infant health indicators [ 63 ] in parenting programs. Thus, strategies should be explored to involve more fathers in PICNIC, as well as grandparents or other family members who may influence child nutrition practices [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of fathers has positively influenced retention and engagement of mothers [ 62 ] and maternal and infant health indicators [ 63 ] in parenting programs. Thus, strategies should be explored to involve more fathers in PICNIC, as well as grandparents or other family members who may influence child nutrition practices [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the complexity of these interventions as well as the lack of information on implementation processes advocate for further studies that provide this additional detail on community mobilization’s implications for ANC/PNC support and uptake. Reviews published as recently as 2021 perpetuate the same pattern by labeling one-sided didactic programs as “community participation” or failing to describe what comprised the community mobilization component of a program [ 73 , 74 ]. Furthermore, while the reviews show a large geographic range in terms of countries and SDG regions included, the relevance of context in community-based interventions emphasizes the importance of considering localized and country/region-specific findings.…”
Section: Discussionmentioning
confidence: 99%
“…Most MCN research and interventions in low-and middle-income countries are not based on in-depth analysis of family systems (Martin, McCann, et al, 2021) and often assume universality of the nuclear family structure. This assumption is based in part on the fact that the household is taken as the unit of analysis and also on the erroneous assumption that household and family are synonymous.…”
Section: Family Systemsmentioning
confidence: 99%
“…A scoping review to identify interventions that engaged family members in maternal and child nutrition reported a substantial increase in the number of studies about interventions to engage family in peer reviewed literature since 2010 (Martin, McCann, et al, 2021). The authors identified 63 unique nutrition-specific and nutrition-sensitive interventions or projects that sought to engage fathers, grandmothers, or other family members in lowand middle-income countries.…”
Section: Articles In This Issuementioning
confidence: 99%
See 1 more Smart Citation